2001
DOI: 10.1016/s0029-7844(01)01566-6
|View full text |Cite
|
Sign up to set email alerts
|

Age- and type-dependent effects of parity on urinary incontinence: the Norwegian EPINCONT study

Abstract: Parity is an important risk factor for female urinary incontinence in fertile and peri- and early postmenopausal ages. Only stress and mixed types of incontinence are associated with parity. All effects of parity seem to disappear in older age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
171
4
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(203 citation statements)
references
References 22 publications
19
171
4
9
Order By: Relevance
“…In contrast to most other studies we only found a rather weak association between parity and stress incontinence. Our finding is, however, in accordance with another recent study of women above the age of 65 years, which found little effect of parity among the elderly [26].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to most other studies we only found a rather weak association between parity and stress incontinence. Our finding is, however, in accordance with another recent study of women above the age of 65 years, which found little effect of parity among the elderly [26].…”
Section: Discussionsupporting
confidence: 92%
“…La paridad y el mecanismo de parto son factores de riesgo establecidos para IU, especialmente para IUE 1,2,4,7,23,34,36,37 . En este estudio no observamos una asociación significativa, pero si una tendencia mayor a presentar IU en las mujeres con al menos un embarazo.…”
Section: Discussionunclassified
“…Furthermore, this study found that women aged over 50 had no protective eff ect from cesarean section anymore 12 . Other factors that may have unfavorable infl uence are older age at fi rst childbirth and primiparity 36,37 . In the previously mentioned study by Rortveit et al, the incidence of stress urinary incontinence was 4.7%, 6.9% and 12.2% in the nulliparous, cesarean section and vaginal delivery groups, respectively.…”
Section: Impact Of Pregnancy and Delivery On Urinary Incontinencementioning
confidence: 99%